Book Review: Nicolas Bommarito, Inner Virtue. (January 2019) - Karp, Max
Nicolas Bommarito, Inner Virtue . New York, NY: Oxford University Press, 2017. 208 pages. 55.00 (hardback). ISBN: 9780190673383.